Role of hydrogen sulfide in the male reproductive system - Song, Yunjia; Mao, Caiyun; Zhong, Qing; Zhang, Rong; Jiang, Deyou; Sun, Xutao (Frontiers in Endocrinology, 2024)
As an important gas signaling molecule, hydrogen sulfide (H2S) affects multiple organ systems, including the nervous, cardiovascular, digestive, and genitourinary, reproductive systems. In particular, H2S not only regulates female reproductive function but also holds great promise in the treatment of male reproductive diseases and disorders, such as erectile dysfunction, prostate cancer, varicocele, and infertility. In this review, we summarize the relationship between H2S and male reproductive organs, including the penis, testis, prostate, vas deferens, and epididymis. As lower urinary tract symptoms have a significant impact on penile erection disorders, we also address the potential ameliorative effects of H2S in erectile dysfunction resulting from bladder disease. Additionally, we discuss the regulatory role of H2S in cavernous smooth muscle relaxation, which involves the NO/cGMP pathway, the RhoA/Rho-kinase pathway, and K + channel activation. Recently, various compounds that can alleviate erectile dysfunction have been reported to be at least partly dependent on H2S. Therefore, understanding the role of H2S in the male reproductive system may help develop novel strategies for the clinical treatment of male reproductive system diseases.